Agile Processes in Software Engineering and Extreme Programming: 18th International Conference, XP 2017, Cologne, Germany, May 22-26, 2017, Proceedings - Baumeister, Hubert; Lichter, Horst; Riebisch, Matthias (Lecture Notes in Business Information Processing, 2017)
agile software development; lean development; scrum; project management; software development